DYSLIPIDEMIA AND CARDIOVASCULAR DISEASE RISK (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Dyslipidemia represents a fundamental pathophysiologic mechanism underlying cardiovascular disease development and remains a critical modifiable risk factor in contemporary clinical practice. This comprehensive analysis examines the complex relationship between lipid metabolism disorders and cardiovascular risk, incorporating recent evidence from major clinical trials and population-based studies conducted between 2020 and 2024. The article explores the molecular mechanisms of atherogenesis, current diagnostic approaches, and evidence-based therapeutic interventions including novel pharmacologic agents and precision medicine strategies. Contemporary guidelines emphasize individualized risk assessment incorporating traditional lipid parameters alongside emerging biomarkers and genetic predisposition factors. Recent clinical evidence demonstrates significant cardiovascular benefit from aggressive low-density lipoprotein cholesterol reduction using combination therapies including proprotein convertase subtilisin/kexin type 9 inhibitors and novel small interfering ribonucleic acid therapeutics. The analysis addresses special populations including pediatric patients with familial hypercholesterolemia and individuals with diabetes mellitus, highlighting the importance of early intervention and comprehensive risk modification strategies. Current evidence supports a multifaceted approach combining lifestyle interventions, optimal medical therapy, and emerging technologies for cardiovascular risk reduction in dyslipidemic patients.